The impact of sovereign credit ratings on capital flows and financial markets in Africa - Ntswane, Lesley (My University, 2015)
Defined as an opinion by the rating agencies on the ability and willingness of a sovereign government to meet financial commitments in full and at an agreed time, a number of studies argue that sovereign credit ratings are a de facto requirement for gaining access to international capital (Cantor & Packer, 1995; Larraín, Reisen & Von Maltzan, 1997; Siddiqi, 2007), While a number of studies such as that by Kaminsky and Schmukler (2002) have tested the short-term announcement impact of the sovereign credit rating adjustments on the bond and equity returns. Kim and Wu (2008) attempted to close this knowledge gap by investigating the impact of S&P issued sovereign credit ratings on emerging economies’ financial markets and different types of capital flows. In addition, studies on sovereign credit ratings focus on emerging economies, leaving out a majority of the African countries that are largely classified as developing economies. Accordingly, the primary aim of the present study is to investigate the relationship between Fitch, Moody’s and S&P issued long-term foreign currency sovereign credit ratings and the different types of capital flows in Africa. In addition, the study investigates how the imminent and actual rating migration announcement by Fitch, Moody’s and S&P impact the aggregate equity stocks and nominal exchange rate returns in Africa.The study addresses these two questions by using a comprehensive data set of long-term foreign currency sovereign credit ratings issued by Fitch, Moody’s and S&P on a cross-section of 28 African countries, between 1994 and 2011. Through a panel data regression framework, the study investigates the long-term influence of long-term foreign currency sovereign credit ratings on the different types of capital flows (foreign direct investment, portfolio equity, portfolio bond and commercial bank and other private institutions) while controlling for economic and country governance factors. The second question of the study is addressed by applying event study analysis, to test the transitory impact of long-term foreign currency sovereign credit ratings daily aggregate equity stock returns and nominal foreign exchange rate. Overall, the empirical analysis demonstrates that the history of the portfolio equity, FDI and borrowings from commercial banks and other private institutions, represented by the lag of the capital flows, is the most significant variable determinant of these types of flows. For the vi borrowings from commercial banks and other private institutions, empirical evidence also suggests that debt rescheduling is a significant determinant for future access to this type of capital. Long-term foreign currency sovereign credit ratings issued by Fitch, Moody’s and S&P on the other hand, show a marginal influence on the portfolio equity, FDI and borrowings from commercial banks and other private institution capital flows with the RATING variable reinforcing, as opposed to substituting, for the primary determinants of these types of capital flows. For the public and publicly guaranteed and non-guaranteed portfolio bond flows, where, except for South Africa, many African countries have a limited history of borrowing from the international bond markets, the lag of the dependent variable is insignificant. Empirical evidence further shows that the public and publicly guaranteed and non-guaranteed portfolio bond flows respond differently to the long-term foreign currency sovereign credit ratings issued by the different rating agencies. While S&P issued RATINGS variable is significant for the public and publicly guaranteed portfolio bond net flow rates (PPGBOND) model, when South Africa is excluded from the sample, Fitch issued RATINGS variable is significant for the non-guaranteed portfolio bond net flow rates (PNGBOND). Interestingly, the empirical evidence show that South Africa’s Fitch, Moody’s and S&P issued RATINGS have a positive relationship with both portfolio bond and commercial bank and other private institutions net flow rates to countries other than South Africa. In particular, the public and publicly guaranteed portfolio bond (PPGBOND) and commercial bank and other private institutions net flow rates (PPGCOMM) for countries other than South Africa, respond positively to the S&P and Fitch issued South Africa RATING, with own country RATING becoming insignificant when the S&P issued South African RATING is introduced to the model. Similarly both the PPGCOMM and PNGBOND net flow rates to countries other than South Africa, respond positively to the Moody’s issued South African RATING. Event study analysis show that long-term foreign currency sovereign credit ratings upgrade, downgrades eminent rating changes have a short-term announcement impact on both the aggregate equity stock and nominal foreign exchange rate returns in Africa. In particular, the event study results show that there is an incentive for a positive rating announcement for below investment grade ratings while there is no punishment for a negative rating announcement.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.